PENGARUH INVESTASI, PENDIDIKAN, PERTUMBUHAN PENDUDUK, DAN EKSPOR TERHADAP PERTUMBUHAN EKONOMI 24 NEGARA ASIA PERIODE 2004-2013 - Ivon Kristin Nip; Suyanto Suyanto; Made Siti Sundari (Jurnal Ekonomi dan Bisnis, 2016)
The purpose of this study is to examine and to analyze the impact of Investment, Education, Population Growth, Primary Export, and Manufacturing Export to Economic Growth of 24 countries in Asia. The data analyzes under the total 24 countries and disaggregate grouped on developing countries and developed countries. This study utilizes a quantitative research approach and the method of analysis is data Ordinary Least Square (OLS) for panel data. 24 countries in Asia for period 2004-2013 are used as the sample set. The result indicates that Investment, Population Growth, and Manufacturing Export have significanteffect on Economic Growth in developing country. In addition, Investment, Education, and Primary Export significanteffect on Economic Growth in developed country. The results imply lead a country must give support to the government for improve climate and policies investment as well as improve the education system and quality to encourage sustainable economic growth.